Implementation of Islamic Education Management in Integrating Da'wah, Education and Regeneration at the Kauman Muhammadiyah Islamic Boarding School in Padang Panjang - Muchtar, Risman; Andriyani , Andriyani; Suradika, Agus; Bahri, Saiful; Nurmalia, Nurmalia (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study aims to analyze the implementation of Islamic education management in integrating da'wah, teaching and cadre in Kauman Muhammadiyah Padang Panjang Islamic Boarding School. The main issue in this study is how the Islamic education management system is applied to harmonize these three aspects in order to produce a generation of Muslims who are knowledgeable, noble and ready to preach. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, in-depth interviews and documentation studies of various policies and programs implemented in Islamic boarding schools. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, in-depth interviews and documentation studies of various policies and programs implemented in Islamic boarding schools. The results showed that the integration of da'wah, teaching and cadre at Kauman Muhammadiyah Padang Panjang Islamic Boarding School is carried out through an Islamic values-based curriculum, which combines academic learning and character building. Extracurricular activities such as recitation and leadership training also support the cadre process. The management of Islamic education in this boarding school emphasizes teaching methods based on the Qur'an and Sunnah, as well as strengthening da'wah through various media, religious forums and involving students in social activities. The conclusion of this research confirms that the implementation of Islamic education management in Kauman Muhammadiyah Padang Panjang Islamic Boarding School has succeeded in creating synergy between da'wah, teaching and cadre. However, there are still challenges in optimizing technology and learning methods to be more in line with current developments